A Kinetic Approach for Assessing the Uptake of Ag from Pristine and Sulfidized Ag Nanomaterials to Plants. (4th May 2021) - Lahive, E.; Schultz, C.L.; Van Gestel, C.A.M.; Robinson, A.; Horton, A.A.; Spurgeon, D.J.; Svendsen, C.; Busquets‐Fité, M.; Matzke, M.; Green Etxabe, A.
Abstract: Nanomaterials (NMs) are thermodynamically unstable by nature, and exposure of soil organisms to NMs in the terrestrial environment cannot be assumed constant. Thus, steady‐state conditions may not apply to NMs, and bioaccumulation modeling for uptake should follow a dynamic approach. The one‐compartment model allows the uptake and elimination of a chemical to be determined, while also permitting changes in exposure and growth to be taken into account. The aim of the present study was to investigate the accumulation of Ag from different Ag NM types (20 nm Ag 0 NMs, 50 nm Ag 0 NMs, and 25 nm Ag2 S NMs) in the crop plant wheat ( Triticum aestivum ). Seeds were emerged in contaminated soils (3 or 10 mg Ag/kg dry soil, nominal) and plants grown for up to 42 d postemergence. Plant roots and shoots were collected after 1, 7, 14, 21, and 42 d postemergence; and total Ag was measured. Soil porewater Ag concentrations were also measured at each sampling time. Using the plant growth rates in the different treatments and the changing porewater concentrations as parameters, the one‐compartment model was used to estimate the uptake and elimination of Ag from the plant tissues. The best fit of the model to the data included growth rate and porewater concentration decline, while showing elimination of Ag to be close to zero. Uptake was highest for Ag 0 NMs, and size did not influence their uptake rates. Accumulation of Ag from Ag2 S NMs was lower, as reflected by the lower porewater concentrations. Environ Toxicol Chem 2021;40:1859–1870. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.